The Analysis of EFL in Curriculum of 2013 - Wilda Cahyani; Rahmadi Nirwanto; Zaitun Qamariah (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This article aims to speak about the history of curriculum in 2013. crucial components associated with the implementation of education. The curriculum as a planning device and gadget concerning goals, content, substances and methods used inside the learning and coaching manner to obtain academic goals has an critical position in countrywide training, therefore gaining knowledge of English is likewise included inside the curriculum in Indonesia. because they want to create a future technology that could compete on the international degree inside the generation of globalization, English lessons in simple schools had been removed and English classes at the junior and senior high faculty levels had been decreased inside the 2013 curriculum. The cause of this examine became to analyze diverse English language mastering rules in Indonesia within the attitude of forming world citizens with intercultural competence because being a international citizen in the era of globalization is a reality. The curriculum as a aspect of training is dynamic, constantly converting through the years. this modification could be very critical along side changes in society, pupil wishes, and tendencies in technological know-how and era. The history of the curriculum compiles methods of training in international locations consisting of Indonesia that can replicate the usa's improvement.